Cell‐specific expression of runt‐related transcription factor 2 contributes to pulmonary fibrosis. Issue 2 (4th January 2018) - Mümmler, Carlo; Burgy, Olivier; Hermann, Sarah; Mutze, Kathrin; Günther, Andreas; Königshoff, Melanie
Abstract : Idiopathic pulmonary fibrosis (IPF) is a fatal lung disease with limited therapeutic options and unknown etiology. IPF is characterized by epithelial cell injury, impaired cellular crosstalk between epithelial cells and fibroblasts, and the formation of fibroblast foci with increased extracellular matrix deposition (ECM). We investigated the role of runt‐related transcription factor 2 (RUNX2), a master regulator of bone development that has been linked to profibrotic signaling. RUNX2 expression was up‐regulated in lung homogenates from patients with IPF and in experimental bleomycin‐induced lung fibrosis. The RUNX2 level correlated with disease severity as measured by decreased diffusing capacity and increased levels of the IPF biomarker, matrix metalloproteinase 7. Nuclear RUNX2 was observed in prosurfactant protein C–positive hyperplastic epithelial cells and was rarely found in myofibroblasts. We discovered an up‐regulation of RUNX2 in fibrotic alveolar epithelial type II (ATII) cells as well as an increase of RUNX2‐negative fibroblasts in experimental and human pulmonary fibrosis. Functionally, small interfering RNA–mediated RUNX2 knockdown decreased profibrotic ATII cell function, such as proliferation and migration, whereas fibroblasts displayed activation markers and increased ECM expression after RUNX2 knockdown. This study reveals that RUNX2 is differentially expressed in ATII cells vs. fibroblasts in lung fibrosis, which contributes to profibrotic cell function. Cell‐specific targeting of RUNX2 pathways may represent a therapeutic approach for IPF.—Mümmler, C., Burgy, O., Hermann, S., Mutze, K., Günther, A., Königshoff, M. Cell‐specific expression of runt‐related transcription factor 2 contributes to pulmonary fibrosis. FASEB J. 32, 703–716 (2018). www.fasebj.org